Modeling Effects of Heated Waste Water Discharge Rate on the Thermal Plume Pattern and Temperature at the Wastewater Discharge Site - parasto akbari; masood sadri nasab; y nikpor; a s (مهندسی منابع آب, 2018)
Water application as a coolant in industry and its discharge in the water ecosystem causesthermal pollution. This study aimed at investigating the water temperature pattern affected byheated wastewater discharge rate changes using the three dimensional CoupledHydrodynamical-Ecological model for Regional and Shelf Seas (COHERENS). The model wasrun for two years to reach a steady state employing a Cartesian grid (40 × 120), five sigmalevels from the surface to the bottom, meteorological data, main components of the tide (O1,K1, M2, S2), and information related to the heated wastewater discharge rate and temperatureof water body. The modeling results showed that the wastewater discharge rate affected thetemperature at the discharge site and thermal plume expansion in the different seasons. The rateof temperature variations that were created in the environment by the heated wastewaterdepended on the temperature difference between the environment and wastewater. The resultsalso showed the Coriolis force had an effect on the thermal plume. Consequently, the plumeand its effects on water body had been diverted to the right. The results of this modeling can beused to manage thermal pollution in the environment and improve the efficiency of the coolingsystem used in industry.Keyword: Modeling, Heated Wastewater, Temperature Field, Cooling System.